THE INFLUENCE OF ORGANIZATIONAL CULTURE AND LEADERSHIP TO JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE PERFORMANCE OF OFFICE OF RELIGIOUS AFFAIRS IN CILACAP DISTRICT - Maman Sulaeman (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2018)
Achievement of KUA performance in Cilacap Regency has not met expectations. These conditions can be improved and need to be evaluated and research on the quality of human resources so that policies taken in the future can improve the performance of employees and minimize factors that can reduce employee performance. The purpose of this study is to determine the influence of organizational culture and leadership on job satisfaction and its impact on employee performance. The method used is path analysis, which is to get the picture, relationship pattern and influence of research variables that have been determined. The result showed that organizational culture had a positive effect on employee satisfaction of 73.4%. Leadership positive effect on employee satisfaction of 73.4%. Organizational culture and leadership have a positive effect on employee satisfaction of 75.7%. Organizational culture and leadership through a positive effect on employee performance through employee satisfaction of 85.2%.